The effect of surface polarity of glass on liquid crystal alignment. Issue 5 (9th April 2018) - Kim, Youngju; Lee, Mongryong; Wang, Hyuck Sik; Song, Kigook
ABSTRACT: The effects of the surface polarity of a glass substrate on the orientation of nematic liquid crystals (LCs) were studied using the polarised optical microscope and Fourier-transform infrared spectroscopy. On the surface of oxygen plasma treated glass, a homeotropic alignment of LCs was induced for LCs with negative dielectric anisotropy. This suggests that vertical orientation of LCs could be induced on a polar glass substrate without using an LC alignment layer. Upon cooling towards the isotropic–nematic transition, E7 with positive dielectric anisotropy changes its LC arrangement to isotropic, homeotropic, planar orientations in order. The nematic LC anchoring transition of E7 was interpreted by considering the competition between van der Waals forces and dipole interactions that control the alignment of LC molecules on a polar glass surface. Graphical Abstract: